Therapeutic relationship and concordance of client- and clinician-rated motivational goals in treatment of people with psychosis: an exploratory study. Issue 2 (3rd April 2018) - Cavelti, Marialuisa; Tschümperlin, Raphaela M.; Hubl, Daniela; Kupper, Zeno; Caspar, Franz; Westermann, Stefan
ABSTRACT: Addressing motives determining behavior and experiences of people in treatment for psychosis could improve the therapeutic relationship. This pilot study explored the association between the concordance of clients' and clinicians' ratings of clients' motivational goals and the therapeutic relationship in the treatment of psychosis. Twenty in- and outpatients diagnosed with a psychotic disorder in a general psychiatric setting answered measures addressing motivational goals and the therapeutic relationship. Fifteen clinicians rated their clients' motivational goals and psychopathology. The concordance between clients' and clinicians' ratings of approach goals was not associated with clients' ratings of the therapeutic relationship. However, a higher concordance in avoidance goals ratings was significantly correlated with less satisfaction with the therapeutic relationship. This finding might be understood in light of explicit (i.e. conscious) and implicit (i.e. non-conscious) avoidance goals: The more difficulties clinicians had in recognizing their clients' implicit goals, the more they may have only rated and considered the clients' explicit goals. This could have resulted in both a higher concordance rating between clients and clinicians, and less client satisfaction with the therapeutic relationship (because of unintended threats for implicit avoidance goals). Future studies with larger samples are needed that separately examine explicit and implicit motivational goals of people in treatment for psychosis.